2017
DOI: 10.1111/bjh.14882
|View full text |Cite
|
Sign up to set email alerts
|

Long non‐coding RNA MALAT1 is an inducible stress response gene associated with extramedullary spread and poor prognosis of multiple myeloma

Abstract: Extramedullary myeloma (EMM) occurs when myeloma develops outside the bone marrow; it often develops after chemotherapy and is associated with the acquisition of chemo-resistance and a fatal course. The mechanisms underlying extramedullary spread have not yet been fully elucidated. MALAT1 is a highly abundantly and ubiquitously expressed long non-coding RNA that plays important roles in cancer metastasis. The aims of this study were to clarify the association of MALAT1 with EMM and to elucidate the underlying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 52 publications
(82 reference statements)
2
63
0
Order By: Relevance
“…Many studies have shown that lncRNAs are dysregulated in cancer and involved in oncogenic or tumor inhibitory processes (15). The aberrant lncRNAs expression including OIP5-AS1 (16), MALAT1 (17,18), MEG3 (19), CRNDE (20), H19 (21), UCA1 (22), and PACT1 (23) have been reported in MM. However, the investigation of lncRNA in MM is still in primary, and the understanding of their biological function needs to be progressively elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that lncRNAs are dysregulated in cancer and involved in oncogenic or tumor inhibitory processes (15). The aberrant lncRNAs expression including OIP5-AS1 (16), MALAT1 (17,18), MEG3 (19), CRNDE (20), H19 (21), UCA1 (22), and PACT1 (23) have been reported in MM. However, the investigation of lncRNA in MM is still in primary, and the understanding of their biological function needs to be progressively elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…36,37 It is a poor prognostic factor in myeloma oncogenesis, and its expression increases with disease progression. [30][31][32] It is known that KDM3A promotes MALAT1 transcription by demethylating histones at its promoter region in neuroblastoma, and its upregulation could contribute to metastasis. 33 Furthermore, it has been shown that KDM3A-MALAT1-MAPK signaling contributes to cell proliferation in gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…These genes included those already known to act as oncogenes in myeloma, such as IGF1 and MAF (supplemental Table 5). Of the remaining candidate genes, the long noncoding RNA MALAT1 was of particular interest because it has been reported to be a poor prognostic factor in myeloma 30,31 and is involved in various antiapoptotic pathways in myeloma oncogenesis. 32 As expected, MALAT1 was upregulated during hypoxia in all 8 myeloma cell lines ( Figure 4B).…”
Section: Knockdown Of Kdm3a Induces Apoptosis In Myeloma Cells Under mentioning
confidence: 99%
“…This means that MALAT1 expression may serve as a molecular predictor for patients. Furthermore, MALAT1 expression was markedly higher in extramedullary myeloma (EMM), when compared to intramedullary myeloma cells . It was also found that MALAT1 expression level was positively correlated with the mRNA levels of HSP90, which has been reported to be induced by bortezomib, and contributes to drug resistance .…”
Section: Mechanisms Of Lncrnas In MMmentioning
confidence: 96%